2012
DOI: 10.1016/j.neuroimage.2012.03.088
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural complexity and life course cognitive change

Abstract: Fractal measures such as fractal dimension (FD) can quantify the structural complexity of the brain. These have been used in clinical neuroscience to investigate brain development, ageing and in studies of psychiatric and neurological disorders. Here, we examined associations between the FD of white matter and cognitive changes across the life course in the absence of detectable brain disease. The FD was calculated from segmented cerebral white matter MR images in 217 subjects aged about 68years, in whom archi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 46 publications
4
41
0
Order By: Relevance
“…When we introduced childhood ability into our model, RPM and the general factor (g) became significant. This result is essentially a confirmation of a previous work (Mustafa et al, 2012) but with additional longitudinal data. That is, that structural complexity is associated with lifelong cognitive differences.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…When we introduced childhood ability into our model, RPM and the general factor (g) became significant. This result is essentially a confirmation of a previous work (Mustafa et al, 2012) but with additional longitudinal data. That is, that structural complexity is associated with lifelong cognitive differences.…”
Section: Discussionsupporting
confidence: 90%
“…Cortical complexity measured by FD is also positively correlated with the number of years of education and the intelligence quotient (Im et al, 2006). Brain complexity has also provided an insight into variation of cognitive performance throughout the human life span (Mustafa et al, 2012). FD thus provides information that is complementary to volumetric measurements of the brain and correlates with aging, cognitive ability and presence of neurological disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, fractal dimension within the CNS increases with childhood and adolescence, and then decreases in association with age, [44] which parallels the rise and fall in entropy production over the same time frames [77] as well as the decrease in glucose metabolism with age [72,81,82]. Moreover, fractal studies have demonstrated a decrease in fractal dimension of the CNS with illness (i.e., Alzheimer's [42], epilepsy [23,24], MS [45], stroke [49]) which correlates with metabolic studies demonstrating a decline in glucose metabolism with illness [83,85,88,[90][91][92][93][94][95][96][97][101][102][103].…”
Section: Discussionmentioning
confidence: 99%
“…In fact in 2001, Blanton and colleagues demonstrated that the complexity of the cortex folding characterized by fractal dimension increases with normal brain development over the first two decades of life in normal children [41]. In relation to cognitive changes and age, a study on the association of fractal dimension and white matter of the brain revealed that subjects with greater white matter complexity have greater than expected fluid abilities than predicted by their childhood intelligence and less cognitive decline between the ages of 11 and 68 years of age [44]. A study on the quantitative evaluation of age-related white matter microstructural changes on MRI multifractal analysis revealed a significant increase in both heterogeneity of the frontal lobes and executive dysfunction scores in healthy elderly subjects compared to young healthy subjects, suggesting that microstructural changes in the white matter preferentially occur in the frontal region with normal aging, and that these changes are associated with executive cognitive decline related to subcortical dysfunction [43].…”
Section: Agingmentioning
confidence: 99%